Evaluasi Program Pembinaan Penghuni Asrama Calasanz di Nekafehan-Atambua Tahun 2024 dan Implikasinya Bagi Program Pengelolaan Asrama - En, Hendrika Buik; Margretha, Dhiu; Nagul, Wens (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study evaluates the implementation of the coaching program for Calasanz dormitory residents in Nekafehan-Atambua and the impact on the effectiveness of its coaching. Therefore, some of the problems are general problems: How is the implementation of coaching for Calasanz dormitory residents in 2024 and its implications for the coaching program? Specific Problems: How is the planning of the coaching program, the implementation of the coaching program, the evaluation and follow-up of the coaching program, and the implications for the mentoring program? The objectives of this study are: 1). General objective: To determine the implementation of coaching for Calasanz dormitory residents in 2024 and its implications for the mentoring program. 2). Specific Objectives: to determine the planning of the coaching program, the implementation of the coaching program, the evaluation and follow-up of the coaching program and its implications for the mentoring program. The method used in this study is qualitative research with data collection techniques in the form of observation, interviews, and documentation studies. The informants in this study were 1) the general manager, 2) the dormitory supervisor and mentor, 3) the dormitory residents. The results of the study showed that coaching for Calasanz dormitory residents was carried out through the stages of planning, implementation, evaluation and follow-up. However, this study only uses qualitative methods so it does not include qualitative analysis of the impact of coaching on changes in the behavior of dormitory residents. The results of this study recommend increasing the number of mentors, optimizing activity schedules, and providing more complete supporting facilities to support the effectiveness of the coaching program.ABSTRAKPenelitian ini mengevaluasi penyelenggaraan program pembinaan bagi penghuni asrama Calasanz di Nekafehan-Atambua dan dampak terhadap efektivitas pembinaannya. Maka itu Adapun beberapa permasalahannya yaitu masalah umum: Bagaimana penyelenggaraan pembinaan penghuni asrama Calasanz tahun 2024 dan implikasinya bagi program pembinaan? Masalah Khusus: Bagaimana perencanaan program pembinaan, pelaksanaan program pembinaan, evaluasi dan tindak lanjut program pembinaan, dan implikasi bagi program pendampingan? Adapun tujuan dalam penelitian ini, yaitu: 1). Tujuan umum: Untuk mengetahui penyelenggaraan pembinaan penghuni asrama Calasanz tahun 2024 dan implikasinya bagi program pendampingan. 2). Tujuan Khusus: untuk mengetahui perencanaan program pembinaan, pelaksanaan program pembinaan, evaluasi dan tindak lanjut program pembinaan dan implikasinya bagi program pendampingan. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan studi dokumentasi. Informan dalam penelitian ini adalah 1) penanggung jawab umum, 2) pembina asrama dan pendamping, 3) penghuni asrama. Hasil penelitian menunjukkan bahwa pembinaan bagi penghuni asrama Calasanz diselenggarakan melalui tahap perencanaan, pelaksanaan, evaluasi dan tindak lanjut. Namun, penelitian ini hanya menggunakan metode kualitatif sehingga belum mencakup analisis kualitatif mengenai dampak pembinaan terhadap perubahan prilaku penghuni asrama hasil penelitian ini merekomendasikan peningkatan jumlah Pembina, optimalisasi jadwal kegiatan, serta penyediaan sarana pendukung yang lebih lengkap untuk menunjang efektifitas program pembinaan.